Dimethyl Fumarate Ameliorates Nucleus Pulposus Cell Dysfunction through Activating the Nrf2/HO-1 Pathway in Intervertebral Disc Degeneration - Ruihong Wang (Hindawi Limited, 2021)
Background. Oxidative stress, inflammation, and nucleus pulposus cells (NPCs) apoptosis are involved in pathogenesis of intervertebral disc (IVD) degeneration (IVDD). Dimethyl fumarate (DMF) has been found to effectively depress oxidative stress and inflammation via the Nrf2 pathway. Hence, this project was designed to explore the underlying mechanisms of how DMF protects NPCs from damage by LPS challenge. Methods and Results. CCK8 assay and flow cytometry of apoptosis indicated that DMF treatment attenuated LPS-induced NPC damage. Western blot analysis demonstrated that DMF enhanced the expressions of nuclear factor-erythroid 2-related factor 2 (Nrf2) and heme oxygenase-1 (HO-1) in LPS-challenged NPCs. DMF treatment significantly decreased the accumulation of ROS, downregulated inflammatory cytokines (p-NF-κB, IL-1β, and TNF-α), and ER stress-associated apoptosis proteins (Bip, calpain-1, caspase-12, caspase-3, and Bax) in LPS-challenged NPCs. The level of antiapoptotic protein Bcl-2 was promoted by DMF treatment in LPS-challenged NPCs. Glutathione (GSH) assay showed that DMF treatment improved reduced to oxidized glutathione ratio in LPS-challenged NPCs. Furthermore, the results of western blot analysis indicated that in LPS-challenged NPCs, DMF treatment ameliorated the elevated levels of matrix degradation enzymes (MMP-13, aggrecanase 1) and type I collagen and the reduced levels of matrix composition (type II collagen and ACAN). However, Nrf2 knockdown abolished these protective effects of DMF. Conclusion. Our data suggested that treatment with DMF mitigated LPS-induced oxidative stress, inflammation, and ER stress-associated apoptosis in NPCs via the Nrf2/HO-1 signaling pathway, thus reliving LPS-induced dysfunction of NPCs, which offered a novel potential pharmacological treatment strategy for IVDD.